Economic Vulnerabilities of Fishing-Dependent Households around Laguna Lake, Philippines - Palanca-Tan, Rosalina (Archīum Ateneo, 2020)
The study characterizes the mainly subsistence fishing communities surrounding Laguna Lake and provides empirical evidence of the economic deprivation that they are experiencing using survey data. Following a multi-dimensional approach, the paper focuses on consumption expenditures as the prime indicator of economic well-being – together with assets ownership, financial behavior, and social engagements. Regression analyses are conducted to identify the factors underlying consumption and to determine how different forms of household capital (physical, financial, and social) and fishing activities affect the capacity to generate income or livelihood. The study finds that: 1) food consumption (mainly rice) accounts for half of the household’s total expenditures, is very income-inelastic, and is mainly determined by household size; 2) all consumption expenditures are income-inelastic and are therefore basic necessities, except for mobile phone load, the only luxury consumption expenditure for these low-income fishing households; (3) while derived income (sum of all expenditures and savings) is not significantly determined by any form of capital, it is significantly higher for households undertaking aquaculture; and (4) the conditional cash transfer of the government significantly contributes to household consumption as an income augmentation measure but does not significantly lower food shortage vulnerability of the household.